DESIGN OF A CATALYTIC INCINERATOR - Loayza·Pérez, J. (2003)
The systematizing of a design method developed by Relalliok W.B. (1981) is presented, for the calculation of the basic dimennsions of a catalytic incinerator of mixed channel, taking like reference the theorical development and case mentioned by Benitez J. (1993).